Report by the eleven CGIAR Centers that signed agreements under Article 15 of the Treaty (Appendix 2) - CGIAR Genebank Platform (2019)
This report provides an update on the status of the PGRFA collections maintained by the eleven CGIAR Centers that signed Article 15 agreements with the Governing Body in 2006. As of December 31, 2018, these Centers held over 758,000 accessions of crop, forage, and tree germplasm which they maintain in their genebanks and make available under the SMTA.